Dimerization of the glucan phosphatase laforin requires the participation of cysteine 329. - Pablo Sánchez-Martín (Public Library of Science (PLoS), 2013)
Laforin, encoded by a gene that is mutated in Lafora Disease (LD, OMIM 254780), is a modular protein composed of a carbohydrate-binding module and a dual-specificity phosphatase domain. Laforin is the founding member of the glucan-phosphatase family and regulates the levels of phosphate present in glycogen. Multiple reports have described the capability of laforin to form dimers, although the function of these dimers and their relationship with LD remains unclear. Recent evidence suggests that laforin dimerization depends on redox conditions, suggesting that disulfide bonds are involved in laforin dimerization. Using site-directed mutagenesis we constructed laforin mutants in which individual cysteine residues were replaced by serine and then tested the ability of each protein to dimerize using recombinant protein as well as a mammalian cell culture assay. Laforin-Cys329Ser was the only Cys/Ser mutant unable to form dimers in both assays. We also generated a laforin truncation lacking the last three amino acids, laforin-Cys329X, and this truncation also failed to dimerize. Interestingly, laforin-Cys329Ser and laforin-Cys329X were able to bind glucans, and maintained wild type phosphatase activity against both exogenous and biologically relevant substrates. Furthermore, laforin-Cys329Ser was fully capable of participating in the ubiquitination process driven by a laforin-malin complex. These results suggest that dimerization is not required for laforin phosphatase activity, glucan binding, or for the formation of a functional laforin-malin complex. Cumulatively, these results suggest that cysteine 329 is specifically involved in the dimerization process of laforin. Therefore, the C329S mutant constitutes a valuable tool to analyze the physiological implications of laforin's oligomerization.